Fulfilling the Housing Dreams of Microfinance Clients - Roy, Friedemann; Rao, Shilpa; Bansal, Sachin (World Bank, Washington, DC, 2015)
Rahees Mohammed and his wife lived in a rented house in a slum and had one wish - to build a house that will be a permanent home for the whole family. Aadhar Housing Finance Private Limited can help Rahees realize his dream by offering a housing finance product that corresponded to his needs, preferences, and capacities. This smart lesson, building on Aadhar’s experience and that of other housing finance clients in South Asia, provides a brief overview of the do’s and don’ts for the implementation of housing finance products.